The Fault Lines of Leadership: Lessons from the Global Covid-19 Crisis. Issue 1 (2nd January 2021) - Maak, Thomas; Pless, Nicola M.; Wohlgezogen, Franz
ABSTRACT: In this article, we reflect on the role that leadership has played in the response to the global Covid-19 crisis. We discuss two major 'fault lines' of leadership: narcissism, and ideological rigidity. A fault line is a problem that may not be obvious under normal circumstances but could cause leadership to fail stakeholders and society at large in a defining moment such as a global pandemic. Using case examples from global political leaders we elaborate on these breaking points in crisis leadership and contrast them with the healing properties of leader compassion and mending forces of evidence-based decision making. We conclude our article with implications for responsible leadership research and practice.